1997
DOI: 10.5694/j.1326-5377.1997.tb126674.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of inappropriate use of blood products by prospective monitoring of transfusion request forms

Abstract: Objective To determine the effect of prospective monitoring on appropriateness of transfusions of red cells, platelets and fresh frozen plasma (FFP). Design Prospective interventional study. Setting Royal Melbourne Hospital (a tertiary teaching hospital), Melbourne, Victoria, March‐May 1996. Intervention The blood product request form was modified to Incorporate indications for transfusion and clinical and laboratory data. Requests were monitored by blood bank laboratory staff for conformation with hospital tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 23 publications
3
63
2
2
Order By: Relevance
“…Our finding that a substantial proportion of transfusions were inappropriate is consistent with other studies in Australia 7 9 and elsewhere 10 . ‐ 19 The value of our study is that the results are based on a representative State‐wide sample and provide statistically unbiased estimates for the three major categories of public hospitals.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that a substantial proportion of transfusions were inappropriate is consistent with other studies in Australia 7 9 and elsewhere 10 . ‐ 19 The value of our study is that the results are based on a representative State‐wide sample and provide statistically unbiased estimates for the three major categories of public hospitals.…”
Section: Discussionsupporting
confidence: 92%
“…These and other studies reinforce the importance of the blood bank staff reviewing the indications for blood transfusions as well as the formation of a transfusion committee (29,30) . Other measures that could be adopted to reduce excessive blood consumption include strategies published in the literature that use the descriptors "blood conservation strategies" and "bloodless medicine" (4) .…”
Section: Discussionsupporting
confidence: 60%
“…Tuckfield et al showed a decrease in inadequate indications for RBC concentrates from 16% to 3% after a prospective intervention with careful monitoring of blood bank physicians (29) . These and other studies reinforce the importance of the blood bank staff reviewing the indications for blood transfusions as well as the formation of a transfusion committee (29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…Reversal of warfarin anti‐coagulant effects has emerged as the commonest contributory indication for FFP (34% compared to 4% previously reported from another tertiary referral hospital in Victoria in 1996) 3 . This is likely secondary to an increasing number of, especially elderly, individuals (0.5–1.8% described in two European populations) 4 warfarinized for a variety of cardiovascular indications, such as atrial fibrillation 5 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of guidance of target INR/aPTT and Plt counts in different procedures, compared with other published guidelines 8,9,18 . Uncertainty about the appropriate laboratory criteria may lead to a higher rate of inappropriate FFP transfusions 3 . Thrombocytopenia, as a major contributory factor in bleeding patients, is also imprecise.…”
Section: Discussionmentioning
confidence: 99%